2022
DOI: 10.3390/ijerph19052816
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Contamination: A Growing Threat to Riverine and Urban Communities in the Brazilian Amazon

Abstract: In recent decades, widespread and uncontrolled use of mercury (Hg) in artisanal small-scale gold mining has released thousands of tons of mercury-contaminated waste in the Amazon biome, endangering the largest tropical rainforest worldwide. In this study, we assessed and compared blood Hg levels in individuals living in urban and riverine areas in the lower Tapajós basin and examined the association between Hg exposure and specific biochemical parameters. In total, 462 adults from eight riverine communities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
0
9
0
3
Order By: Relevance
“…The population studied presented a typical food profile of riverside populations in the Amazon region, in which riverine people reported having a good diet (natural food) based on vegetables, Brazil nuts, fruits, and mainly fish, the latter item being consumed three to four times per week [ 55 , 72 ]. We highlight the “fish consumption” factor for two interesting aspects: (i) a positive aspect, since there is a high concentration of unsaturated fats and omega-3 fatty acids in this food, which can substantially contribute to the prevention of cardiovascular diseases in this population, since this nutrient has been proven to prevent this disease [ 38 , 73 ]; and (ii) a negative aspect, since there is a strong possibility that this food is contaminated by methylmercury, which in turn can bioaccumulate in riverine people who consume them [ 39 , 40 , 41 , 42 ]. Indeed, Souza-Araujo and collaborators (2022) [ 42 ] identified fish contamination and mercury biomagnification in food webs in the Belo Monte Hydroelectric Power Plant, in the middle of Xingu River, Pará state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The population studied presented a typical food profile of riverside populations in the Amazon region, in which riverine people reported having a good diet (natural food) based on vegetables, Brazil nuts, fruits, and mainly fish, the latter item being consumed three to four times per week [ 55 , 72 ]. We highlight the “fish consumption” factor for two interesting aspects: (i) a positive aspect, since there is a high concentration of unsaturated fats and omega-3 fatty acids in this food, which can substantially contribute to the prevention of cardiovascular diseases in this population, since this nutrient has been proven to prevent this disease [ 38 , 73 ]; and (ii) a negative aspect, since there is a strong possibility that this food is contaminated by methylmercury, which in turn can bioaccumulate in riverine people who consume them [ 39 , 40 , 41 , 42 ]. Indeed, Souza-Araujo and collaborators (2022) [ 42 ] identified fish contamination and mercury biomagnification in food webs in the Belo Monte Hydroelectric Power Plant, in the middle of Xingu River, Pará state.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Souza-Araujo and collaborators (2022) [ 42 ] identified fish contamination and mercury biomagnification in food webs in the Belo Monte Hydroelectric Power Plant, in the middle of Xingu River, Pará state. Recent studies have reported mercury contamination of traditional (e.g., riverine and indigenous) and urban communities in the lower Tapajós basin and in the Tucurí Lake influence area, Pará state [ 40 , 41 , 74 ]. Therefore, it is possible that the population studied may be at risk of methylmercury contamination, since they may be consuming contaminated fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, this study aimed to evaluate the impact of garimpo activities on Hg contamination in three environmental compartments (sediment, water, and aquatic macrophytes) along a 106-km transect, starting from the point where the mining rafts were seized. Monitoring the impact of small-scale alluvial mining gold mining on Hg contamination is paramount, as garimpo remains the main source of Hg contamination for aquatic ecosystems in Latin America (Meneses et al, 2022 ). Higher Hg concentrations near the points where garimpo rafts were seized and/or seen are expected, as (I) the Hg 0 used in the amalgamation of gold is insoluble in water, and (II) the effects of garimpo are spatially limited (Lechler et al, 2000 ; Guimaraes, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monomethyl-mercury is closely related to fish consumption since it is highly available in aquatic environments, despite constituting only around 1 % of the total mercury pool. This happens because of its highly persistent and lipid-soluble nature, being very bioavailable to fish and easily accumulated especially in fatty tissue, accruing in aquatic food webs and biota in general ( Mataba et al., 2016 ; Govaerts et al., 2018 ; Meneses et al., 2022 ). The consequences of this have been reported in several studies ( Lee et al., 2021 ; Vasconcellos et al., 2021 ; Meneses et al., 2022 ) where people from indigenous communities of the Amazon and, more specifically, the Beni River ( Lee et al., 2021 ) have shown high concentrations of mercury in their bodies.…”
Section: Introductionmentioning
confidence: 99%